ETHNOBOTANICAL STUDY OF JAMU GENDONG IN THE PERSPECTIVE OF THE KULON PASAR COMMUNITY JEMBER KIDUL VILLAGE - Rafiatul Hasanah; Rivo Alfarizi Kurniawan; Mochammad Ricky Rifa'i (Science Education, Institut Agama Islam Negeri Ponorogo, 2023)
Plants have beneficial values for the people of Indonesia. Not a few of the people who use plants as traditional medicine. One traditional medicine that is still there and has been passed down from generation to generation is jamu carrying. The purpose of this research is to describe the local knowledge (ethnobotany) of jamu gendong in the community perspective of Kulon Pasar Desa Jember Kidul. This research was conducted in Kulon Pasar, Jember Kidul Village, Kaliwates District, Jember Regency. The method used in this research is qualitative, with the takeover technique in the form of purposive sampling technique. In addition, it also uses interview and observation techniques to collect data. The results of this study indicate that the people of Kulon Pasar work as jamu sellers. The jamu gendong sold includes kencur rice, keys suroh, ginger, tamarind turmeric, and sinom. Plants that are used in the manufacture of carrying herbal medicine include kencur, ginger, lock, green betel, turmeric, and tamarind. There are five types of herbal medicine from the Zingiberaceae family, two types of herbal medicine from the Fabacae family, one type of herbal medicine from Poaceae, and one type of herbal medicine from the Piperaceae family. Parts of the plant used in the manufacture of carrying herbal medicine are pulp, rhizome, leaves and fruit. Jamu carrying which has benefits to improve body health.